2015
DOI: 10.1016/j.radphyschem.2014.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the polymer molecular weight on the microstructure of hybrid materials prepared by γ-irradiation

Abstract: Hybrid materials have been the object of intense research due to their potential for biomedical applications as well as in other fields. They are usually prepared by sol-gel but the method of gamma irradiation of the precursors is an alternative avoiding the addition of any other chemicals. The study of the hybrids prepared by this method has been progressing to understand the impact of different variables on the microstructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
(16 reference statements)
1
7
0
Order By: Relevance
“…This model also explains the data reported in a previous paper [23] where the influence of the polymer molecular weight was investigated. In a forthcoming paper this model will be extended to the case where the polymer weight distribution is bimodal or very polydisperse and further tested against the collection of data obtained in past and in more recent studies of PDMS-TEOS-PrZr based materials prepared by gamma irradiation with different proportions of the precursors.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This model also explains the data reported in a previous paper [23] where the influence of the polymer molecular weight was investigated. In a forthcoming paper this model will be extended to the case where the polymer weight distribution is bimodal or very polydisperse and further tested against the collection of data obtained in past and in more recent studies of PDMS-TEOS-PrZr based materials prepared by gamma irradiation with different proportions of the precursors.…”
Section: Resultssupporting
confidence: 89%
“…Previously, the authors have studied the role of the OH terminal groups in PDMS [22] and showed that the inorganic oxide cluster sizes and their spatial arrangement scales with the polymer molecular weight [23].…”
Section: Introductionmentioning
confidence: 99%
“…Ionizing radiation is currently used for different applications: medical device sterilization, material modification, heritage preservation, or wastewater treatment, among others. Contrarily to ethylene oxide treatment that can leave toxic residues on treated products, ionizing radiation can be safely used to sterilize healthcare products such as syringes, surgical gloves, or tissue allografts in sealed packages, in order to reduce the microbiological contamination to acceptable levels .…”
Section: Ionizing Radiation Technologiesmentioning
confidence: 99%
“…Contrarily to ethylene oxide treatment that can leave toxic residues on treated products, ionizing radiation can be safely used to sterilize healthcare products such as syringes, surgical gloves, or tissue allografts in sealed packages, in order to reduce the microbiological contamination to acceptable levels . This technology can also be applied on the preparation and functionalization of hybrid materials that are used for biomedical applications and food packaging . On the other hand, Borrely et al (2016) demonstrated that electron-beam radiation was capable of reducing the color (>90% at 2.5 kGy) and toxicity of three different textile effluents and Madureira et al showed the radiolytic degradation of phenolic acids present in wastewaters from the cork industry.…”
Section: Ionizing Radiation Technologiesmentioning
confidence: 99%
See 1 more Smart Citation